BUILDING CLIMATE RESILIENCE: INNOVATIVE STRATEGIES BY INDONESIAN LOCAL GOVERNMENTS - Situmorang, Marningot Tua Natalis; Djaya, Subhan; Astuti, Titin; Hermansyah, Muhammad; Sulistyo, Arif Budi (Alqaprint Jatinangor, 2024)
Climate change is a global challenge that requires rapid and adaptive responses from various levels of government, including local governments. In Indonesia, the role of local governments in building climate resilience is increasingly crucial as the impacts of climate change are felt in various regions. However, bureaucratic barriers, resource constraints, and socio-economic dynamics often hinder the effectiveness of climate resilience strategies at the local level. This study aims to explore the role of local governments in building climate resilience through local policies, technological innovation, and community participation. This study was conducted using a qualitative approach, where data was collected from various sources such as research results and relevant previous studies. The collected data were then processed systematically to find findings that support the development of climate resilience strategies. The results of the study show that local governments have an important role in developing policies that are appropriate to local conditions to deal with climate change. Technological innovation and the development of disaster-resistant infrastructure are key to increasing climate resilience at the local level. Active community participation and community empowerment have also proven to be important factors in implementing effective climate resilience strategies. Bureaucratic barriers and resource constraints can be overcome through cross-regional collaboration that allows for the sharing of knowledge and best practices. Thus, climate resilience strategies at the local level must be based on synergy between government, communities, and the private sector to achieve sustainable and effective results.